The Simulation of the Effect of Rigid Bank Vegetation on the Main Channel Flow - Masouminia, Mohammad Hosein (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
A series of computational hydraulic analyses are applied for the open channels with vertical and inclined banks. During the analyses, riverbank vegetation density on inclined surface were increased to measure the flow hydrodynamic effects of the flow for both, in the inclined riverbank and main channel. The study not only covers the relationship of open channel with vegetated bank, and also proves some of the previous determined results. Additionally, the gathered results illustrate the impacts of vegetation density on riverbank to the entire channel. The longitudinal velocity, turbulence intensity (TI), turbulent kinetic energy and Reynolds stress were presented by figures, to help the outcomes of the results be more readable. The preliminary results are presented in terms of plots, based on the mean velocity along the main flow directon across the channel for ease of comparison between different configurations. The main outcome of the study despicts that, as the river bank vegetation density increases, the mean velocity in the main channel increases, while mean velocity on the river bank decreases. Reynolds stress is an essential part of shear stress in turbulent flows, and the measured Reynolds stresses show that, the stress is higher near bed of the main channel close to the vertical riverbank whereas it shifts to mid flow depths at the region close to the interface of main channel and the inclined riverbank. The turbulence intensity and the turbulence kinetic energy profiles were also showing similarity and parallel behavior with the simulated results of streamwise flow velocities and Reynolds stresses in the main channel and at the inclined riverbank. Keywords: Velocity profile, Reynolds shear stress, Vegetation, Turbulence intensity, Secondary current, Turbulent kinetic energy.

ÖZ : Bir kenarı dik diğer kenarı ise eğimli şev olan açık kanal sisteminde bir dizi nümerik hesaplamalar gerçekleştirilmiştir. Ana kanal içerisindeki hidrodinamik hareketlerin davranışını inceleme amaçlı yapılan bu çalışmada eğimli kenar üzerine rijid elemanlar yerleştirilerek yapay bitki örtüsü yaratılmış ve bu bitki örtüsünün yoğunluğu sürekli artırılmıştır. Açık kanal kenarında yerleştirilen bitkilerin ana kanal içerisindeki etkileri üzerine daha önce deneysel olarak yapılan çalışmaları nümerik olarak modelleme ve etkileri daha detaylı gözlemleme şansı bulunmuştur. Boyuna hız, türbülans yoğunluğu (TI), çalkantılı kinetik enerji ve Reynolds gerilme sonuçları modellenmiş ve çıktılar şekiller aracılığı ile daha okunabilir hale getirilmiştir. Ilk sonuçlar kanal genelinde akım hız profillerinin çıkartılması ve bu profillerin farklı bitki örtüsü yoğunluklarında uğradıkları farklılıkları inceleme amaçlı kullanılmıştır. Ana kanal içerisinde hız profilleri artarken, eğimli kenar yüzeyleri ile bu yüzeylerin kanal ile yaptığı birleşme noktalarında akım hızı azalma göstermiştir. Reynolds gerilmeleri türbülanslı akımlarda kayma gerilmesi tanımlamaları için önem arzetmektedir. Sonuçlar göstermiştir ki ana kanal içerisinde maksimum gerilmeler tabana yakın bölgelerde meydana gelirken, eğimli kenara yaklaşıldığı durumlarda maksimum gerilmeler akım derinliğinin ortalarına doğru kaymaktadır. Türbülans yoğunluğu ve çalkantılı kinetik enerji profilleri akım içerisindeki hız ve gerilme dağılımlarını destekleyen sonuçlar vermiştir. Anahtar Kelimeler: Hız profili, Reynolds kayma gerilmesi, Bitki Örtüsü, Türbülans şiddeti, İkincil akım, Çalkantılı kinetik enerji
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2015. Supervisor: Assoc. Prof. Dr. Umut Türker.
Keywords: Civil Engineering; Channels (Hydraulic engineering); Velocity profile; Reynolds shear stress; Vegetation; Turbulence intensity; Secondary current; Turbulent kinetic energy